Brazilian Guidelines for the pharmacological treatment of patients hospitalized with COVID-19: Joint guideline of Associação Brasileira de Medicina de Emergência, Associação de Medicina Intensiva Brasileira, Associação Médica Brasileira, Sociedade Brasileira de Angiologia e Cirurgia Vascular, Sociedade Brasileira de Infectologia, Sociedade Brasileira de Pneumologia e Tisiologia, Sociedade Brasileira de Reumatologia - Falavigna, Maicon; Stein, Cinara; Luis Gomes do Amaral, José; Cesar Pontes de Azevedo, Luciano; Claudino Belli, Karlyse; Colpani, Verônica; Arns da Cunha, Clovis; Dal-Pizzol, Felipe; Beatriz Souza Dias, Maria; Carvalho Ferreira, Juliana; da Rocha Freitas, Ana Paula; Dalmas Gräf, Débora; et al. (LAJEC - Latin American Journal of Emergency Care, 2022)
Introduction: Several therapies are being used or proposed for COVID-19, and many lack appropriate evaluations of their effectiveness and safety. The purpose of this document is to develop recommendations to support decisions regarding the pharmacological treatment of patients hospitalized with COVID-19 in Brazil. Methods: A group of 27 experts, including representatives of the Ministry of Health and methodologists, created this guideline. The method used for the rapid development of guidelines was based on the adoption and/or adaptation of existing international guidelines (GRADE ADOLOPMENT) and supported by the e-COVID-19 RecMap platform. The quality of the evidence and the preparation of the recommendations followed the GRADE method. Results: Sixteen recommendations were generated. They include strong recommendations for the use of corticosteroids in patients using supplemental oxygen, the use of anticoagulants at prophylactic doses to prevent thromboembolism and the nonuse of antibiotics in patients without suspected bacterial infection. It was not possible to make a recommendation regarding the use of tocilizumab in patients hospitalized with COVID-19 using oxygen due to uncertainties regarding the availability of and access to the drug. Strong recommendations against the use of hydroxychloroquine, convalescent plasma, colchicine, lopinavir + ritonavir and antibiotics in patients without suspected bacterial infection and also conditional recommendations against the use of casirivimab + imdevimab, ivermectin and rendesivir were made. Conclusion: To date, few therapies have proven effective in the treatment of hospitalized patients with COVID-19, and only corticosteroids and prophylaxis for thromboembolism are recommended. Several drugs were considered ineffective and should not be used to provide the best treatment according to the principles of evidence-based medicine and promote economical resource use.